FREQUENCY OF IRON DEFICIENCY ANEMIA IN PREGNANT FEMALES COMING FOR THEIR FIRST ANTENATAL WORK UP IN FIRST TRIMESTER OF PREGNANCY (The Research of Medical Science Review, 2025)
Background: For both the mother and the fetus, iron deficiency anemia can be fatal. Iron status, however, is not frequently assessed during pregnancy. Objective: The aim of this study was to find out the frequency of anemia due to iron deficiency in pregnant women who were attending their first prenatal visit during the first trimester of their pregnancy. Material and methods: The current cross- sectional study was conducted at the Obstetrics and Gynecology Department of Ayub Teaching Hospital, Abbottabad form 1st April to 30 September 2023 after taking permission from the ethical committee of the institute. A total of 141 pregnant women between 18 to 40 years of age coming to OPD or admitted in ward during their 1st antenatal visit in 1st trimester were included. Anemia in patients were confirmed by history and by examination. A blood sample taken was taken from each individual and had their full blood counts (FBCs) performed using a hematology analyzer under supervision of pathologist fellow of CPSP. A Randox kit was used to measure serum ferritin. Data was analyzed using SPSS version 20. Results: A total of 141 pregnant women of different age groups (18-40 years) during their 1st trimester were screened for iron deficiency anemia in this study. Out of the total participants 72(51%) were found anemic. There were no statistically significant variations in the incidence value across the various age groups during the first trimester (P = 0.32). The mean hemoglobin was 9.502 and serum ferritin, 15.83. 37.5%of the patients had severe IDA, whereas 62.5% percent had mild IDA. Conclusion: The current study concluded that iron deficiency anemia is prevalent during pregnancy, with the greatest rate observed in the first trimester. It is still a serious public health concern during pregnancy, and a sizable percentage of anemia in this population is related to iron deficiency. Serious consequences are associated with the iron deficiency anemia on the health of both mother and the developing baby. Theses consequences include increased perinatal mortality, stunted growth, premature births and low birth weight. This all can be prevented by replenishing iron stores of mother. Hence it is indispensable to educate women regarding health promotion.